Ultrafast control of vortex microlasers - Huang, Can; Zhang, Chen; Xiao, Shumin; Wang, Yuhan; Fan, Yubin; Liu, Yilin; Zhang, Nan; Qu, Geyang; Ji, Hongjun; Han, Jiecai; Ge, Li; Kivshar, Yuri; et al. (Science (American Association for the Advancement of Science), 2020)
For applications in ultrafast communication, all-optical switches will require low energy consumption, high speed, a strong modulation ratio, a small footprint, and on-chip integration. Although the small footprint and on-chip integration are accessible, the trade-off between low energy consumption and high speed has been challenging. Huang et al. exploited the idea of bound states in the continuum, effectively a high–quality ( Q ) cavity without the physical cavity, to design vortex lasers with highly directional output and single-mode operation. With the trade-off between low energy consumption and high speed now broken, it should be possible to realize ultrafast optical switching that meets all the requirements of modern classic and quantum information. Science , this issue p. 1018 Ultrafast vortex lasers with highly directional output and single-mode operation have been realized. The development of classical and quantum information–processing technology calls for on-chip integrated sources of structured light. Although integrated vortex microlasers have been previously demonstrated, they remain static and possess relatively high lasing thresholds, making them unsuitable for high-speed optical communication and computing. We introduce perovskite-based vortex microlasers and demonstrate their application to ultrafast all-optical switching at room temperature. By exploiting both mode symmetry and far-field properties, we reveal that the vortex beam lasing can be switched to linearly polarized beam lasing, or vice versa, with switching times of 1 to 1.5 picoseconds and energy consumption that is orders of magnitude lower than in previously demonstrated all-optical switching. Our results provide an approach that breaks the long-standing trade-off between low energy consumption and high-speed nanophotonics, introducing vortex microlasers that are switchable at terahertz frequencies.